11 ILLEGAL DRUG BODY PACKING: RADIOLOGICAL EVALUATION AND MEDICAL MANAGEMENT. (1st March 2006) - De Jesus-Monge, W. E.; Martinez, J.
Abstract : Introduction: Body packing, transportation of illegal drugs by oral ingestion or rectal/vaginal insertion, has been reported in multiple countries. Occasionally, it involves ingestion of multiple drug types at a time. The most commonly transported drugs are cocaine, heroin, amphetamines, and marijuana, among others. Body packers usually carry about 1 kg of drug, divided into 50 to 100 packets of 8 to 10 g each. Each drug packet contains a life-threatening dose of drug. Drug packets are usually identified by abdominal x-rays. Purpose: To describe the radiological evaluation and medical management of body packing based on the case report of 2 patients. Case 1: A 31-year-old male without systemic illness complained of dizziness, nausea, whitish vomit, and diffuse, intermittent, and stabbing abdominal pain. He stated ingestion of more than 100 drug packets, confirmed later by x-rays. The abdomen had bowel sounds present, was diffusely tender to superficial and deep palpation, with voluntary guarding, no rebound, and no hepatomegaly. The patient was treated with gastrointestinal motility agents, and 119 heroin packets were recovered without complication. The patient was discharged from hospital 2 days after admission. Case 2: A 20-year-old male without systemic illness denied any symptom or complaint. He stated ingestion of three to four foreign bodies, confirmed later by x-rays. The abdominal examination was unremarkable. Latex fragments were recovered from stools 6 days after admission, but the patient was clinically unchanged without signs or symptoms of drug intoxication and no drug packet recovery despite therapy. The patient underwent an exploratory laparotomy to remove the drug packets, which were found intact, and was discharged 12 days after admission. Discussion: Body packing involves both genders, children, and pregnant women seeking cash compensation or safe passage into a foreign country. Suspects may be identified through observation, inconsistent statements, intelligence information, and trained personnel. The most life-threatening medical complications are drug intoxication and gastrointestinal obstruction or perforation. Case incidence has increased recently because of increased border and airport security, so the appropriate medical management of these patients is of importance. Travel support was provided by the University of Puerto Rico Post-doctoral Master of Science in Clinical Research Program, Public Health Service grant from the National Institutes of Health, 1R25RR17589.